2013
DOI: 10.2151/jmsj.2013-205
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the East Asian Summer Monsoon Circulation and Precipitation to an Idealized Large-Scale Urban Expansion

Abstract: A numerical simulation was performed here using a regional climate model (RegCM3) at 60-km horizontal resolution to estimate the maximum impact of urbanization in East Asia on the summer monsoon precipitation in China. A new bulk urban parameterization was added into the land-surface scheme to capture the thermal, dynamic, and hydraulic effects of urban land cover. The 9-year simulation results showed that the large-scale change from natural-surface to high-density urban land cover induced an enhancement in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Our results, especially the early summer response of monsoon circulation to the urbanization partly agree with Feng et al (2015). However, the simulated later summer responses of the monsoon circulation are similar to results of Shao et al (2013) and Ma et al (2015). Such a discrepancy can be attributed to different urban scenarios, urban parameterization schemes, numerical models, parameters and so on, which implies that there are still large uncertainties in largescale urban impacts on the monsoon system.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Our results, especially the early summer response of monsoon circulation to the urbanization partly agree with Feng et al (2015). However, the simulated later summer responses of the monsoon circulation are similar to results of Shao et al (2013) and Ma et al (2015). Such a discrepancy can be attributed to different urban scenarios, urban parameterization schemes, numerical models, parameters and so on, which implies that there are still large uncertainties in largescale urban impacts on the monsoon system.…”
Section: Discussionsupporting
confidence: 77%
“…It is worthy noting that Shao et al (2013) suggested that the large-scale changes from natural-surface to high-density urban land cover tend to weaken the summer monsoon, while Feng et al (2015) found that the summer monsoon is slightly strengthened by the large-scale urbanization. Our results, especially the early summer response of monsoon circulation to the urbanization partly agree with Feng et al (2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations